Russia's Asymmetric Response to 21st Century Strategic Competition Robotization of the Armed Forces - Marcinek, Krystyna (RAND, 2023)
The ultimate outcome of the 2022 war in Ukraine and its strategic and economic ramifications are yet to be determined. Arguably, Russia will have to rethink, reform, and rebuild its military while facing even more binding financial constraints under a new wave of sanctions and export controls. In this new environment, Russia's political and military leadership likely will have to prioritize some modernization programs and abandon others. In the past, some Russian military strategists have said that the country's military should not match its adversaries' capabilities; instead, it should seek an asymmetric response by developing capabilities that make its adversaries' high-tech weapon systems economically unjustifiable. In recent years, there seemed to be a growing consensus in Russia that artificial intelligence (AI) and robotics-enabling relatively cheap but capable force-might just be such an asymmetric response. Moreover, in the face of the unsatisfactory performance and low morale of the Russian troops in Ukraine, Moscow might see the robotization of the Armed Forces as a way to alleviate its dependence on manpower. The authors of this report look at Russian views of military applications of robotics and AI and study Russia's motivations for the development of these capabilities. They investigate the degree of autonomy that the Russian military would be willing to delegate to machines, and to what extent the military is willing to replace (rather than augment) human soldiers. Finally, they assess whether Moscow has delivered-or can deliver-on its robotization vision
Title from PDF document (title page; viewed March 14, 2023)
"RAND NATIONAL SECURITY RESEARCH DIVISION
"Prepared for EUCOM - U.S. EUROPEAN COMMAND
Keywords: Artificial intelligence / Military applications / Russia (Federation); Robotics / Military applications / Russia (Federation); Military robots; Drone aircraft; Vehicles, Remotely piloted; Russia (Federation) / Military policy / 21st century; Russia (Federation) / Armed Forces / Robots; Armed Forces / Robots; Artificial intelligence / Military applications; Military policy; Robotics / Military applications; Russia (Federation); 2000-2099